Measurement of the differential cross-section of B+ meson production in pp collisions at √s = 7 TeV at ATLAS - Alconada Verzini, María Josefina (2013)
The production cross-section of B+ mesons is measured as a function of transverse momentum pT and rapidity y in proton-proton collisions at centre-of-mass energy √s = 7 TeV, using 2.4 fb-1 of data recorded with the ATLAS detector at the Large Hadron Collider. The differential production cross-sections, determined in the range 9 GeV < pT < 120 GeV and |y| < 2:25, are compared to next-to-leading-order theoretical predictions.